RELEVANKAH PANCASILA DAN GLOBALISASI? MENGUNGKAP HUBUNGAN PANCASILA DAN IDENTITAS GLOBAL - Maharani Ardi Putri; Eko A Meinarno (Universitas Negeri Malang, 2018)
This article discussed about globalization that eliminated physical borders between coun- tries in the world so that it considered a variable of social change in various fields. One of the important issues related to globalization was whether globalization related to things that were typical of a group, namely the value of the dominant group and has advantages in various aspects of life. Indonesian society has a distinctive value, namely Pancasila. The study method used Pearson correlation analysis to test two significance of two variables, knowing the strong-weak relationship, and knowing the amount of retribution and to explain the degree of relationship between indepen- dent variables with dependent variables. This article also discussed about the measurement the relationship between values formulated in Pancasila and correlated with the global identity. The results obtained that the higher score of Pancasila equal with the person global identity score. This happens to all values of Pancasila. These results could be a marker that the value of Pancasila relevant for Indonesian people in the face of globalization.DOI: http://dx.doi.org/10.17977/um019v3i12018p074